Magnolia kobus var. stellata 'Green Star' 'Green Star' Star Magnolia: FPS-360/FP360, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides a detailed overview of the ‘Green Star’ star magnolia (Magnolia kobus var. stellata ‘Green Star’). It describes the plant’s characteristics, including its size, growth habit, and appearance. The document highlights the plant’s uses, hardiness zones, and planting requirements. It also discusses potential pests and diseases, as well as maintenance tips to ensure healthy growth. Additionally, it mentions other cultivars and hybrids related to the star magnolia. Original publication date October 1999.